Influencing policy change : the experience of health think tanks in low and middle-income countries - Bennett, S. [et al] (2012)
Investigates the contribution made by health policy analyis institutes in low and middle-income countries to health policy agenda setting, formulation, implementation, monitoring and evaluation and assesses which factors support the role of these institutions.